Burden of cancer in the Eastern Mediterranean Region, 2005-2015: findings from the Global Burden of Disease 2015 Study - Fitzmaurice, Christina; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2018)
To estimate incidence, mortality, and disability-adjusted life years (DALYs) caused by cancer in the Eastern Mediterranean Region (EMR) between 2005 and 2015.